The effect of corporate image, customer perceived value, relationship quality and switching intention among Islamic banking customers in Malaysia / Nor Hashima Hashim, Sharifah Latifah Syed A. Kadir - Hashim, Nor Hashima; Syed A. Kadir, Sharifah Latifah (UPENA and Institute of Business Excellence, 2010)
Considerable attention is now given to the concept of relationships between service providers and their customers due to the rapid changing marketing environment and in particular the retail banking sector. The switching behavior phenomena are worth investigating because by assessing switching intentions service providers can implement defensive or offensive marketing strategies for their customers. This study develops and empirically tests for examination of the relationships among corporate image, customer perceived value, relationship quality and switching intention in an Islamic retail banking context. The model is tested using structural equation modeling analysis approach. The conceptual model allows Islamic banking service providers to determine which among the two factors impact switching intention, enabling Islamic service providers to determine appropriate strategies to reduce defection among their bank customers.